Cs2NaGaBr6: a new lead-free and direct band gap halide double perovskite. Issue 30 (5th May 2020) - Saeed, Yasir; Amin, Bin; Khalil, Haleema; Rehman, Fida; Ali, Hazrat; Khan, M. Imtiaz; Mahmood, Asif; Shafiq, M.
Abstract : In this work, we have studied new double perovskite materials, A2 1+ B 2+ B 3+ X6 1−, where A2 1+ = Cs, B 2+ = Li, Na, B 3+ = Al, Ga, In, and X6 1− . Abstract : In this work, we have studied new double perovskite materials, A2 1+ B 2+ B 3+ X6 1−, where A2 1+ = Cs, B 2+ = Li, Na, B 3+ = Al, Ga, In, and X6 1− . We used the all electron full-potential linearized augmented plane wave (FP-LAPW+lo) method within the framework of density functional theory. We used the mBJ approximation and WC-GGA as exchange–correlation functionals. We optimized the lattice constants with WC-GGA. Band structures were calculated with and without spin–orbit coupling (SOC). Further, band structures for Cs2 LiGaBr6 and Cs2 NaGaBr6 were calculated with SOC + mBJ to correct the band gap values with respect to experimental value. We obtained direct bandgaps at Γ-point of 1.966 eV for Cs2 LiGaBr6 and 1.762 eV for Cs2 NaGaBr6, which are similar to the parent organic–inorganic perovskite (MAPI) CH3 NH3 PbI3 ( E g = 1.6 eV). Total and partial density of states were analyzed to understand the orbital contribution of Cs, Na, Li, Ga and Br near the Fermi level. The optical properties in terms of real and imaginary ε, refractive index n, extinction coefficient k, optical conduction σ, absorption I, and reflectivity R were calculated. A study of the elastic and mechanical properties shows that both materials are thermodynamically stable. A stable, direct bandgap and a gap value close to those of MAPI make Cs2 NaGaBr6 a great competitor in the Pb-free hybrid perovskite solar cells world.